2022
DOI: 10.1088/1755-1315/951/1/012113
|View full text |Cite
|
Sign up to set email alerts
|

Cellulase enzyme activity of the bacteria isolated from mangrove ecosystem in Aceh Besar and Banda Aceh

Abstract: Cellulolytic bacteria is one of the beneficial bacteria that can found in mangrove ecosystem. The purposes of study were to analyse the cellulolytic index, and to analyse the cellulase activity of bacteria isolated from soil mangrove. Qualitatively, assessment of cellulase activity were carried out at the Microbiology laboratory of Fish Quarantine Station, Quality Control and Safety of Fishery Products (SKIPM) Aceh, while quantitatively was observed in microbiology laboratory, Biology Department, IPB. Assessme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Our data agree with those of (Fatokun et al 37) who reported that the best agitation rate for xylanase was 150 rpm and for cellulase was between 100 and 150 rpm. Nutrient supplies have been reported to be key elements in the synthesis of cellulase and xylanase, and carbon source is thought to be an essential nutrient affecting enzyme production (45). We tested the impact of different carbon sources, such as glucose, sucrose, mannose, arabinose, lactose, CMC, xylan, glucose + CMC, glucose + xylan and filter paper on enzyme production.…”
Section: Discussionmentioning
confidence: 99%
“…Our data agree with those of (Fatokun et al 37) who reported that the best agitation rate for xylanase was 150 rpm and for cellulase was between 100 and 150 rpm. Nutrient supplies have been reported to be key elements in the synthesis of cellulase and xylanase, and carbon source is thought to be an essential nutrient affecting enzyme production (45). We tested the impact of different carbon sources, such as glucose, sucrose, mannose, arabinose, lactose, CMC, xylan, glucose + CMC, glucose + xylan and filter paper on enzyme production.…”
Section: Discussionmentioning
confidence: 99%
“…1). The pectinolytic index produced by isolates ranged from 0 -0.22 and was classified as low according to Dewiyanti et al [18]. The isolate that had the highest pectinolytic index was Y5, but there were no significant differences in value between isolates.…”
Section: Selection Of Pectinolytic Yeastmentioning
confidence: 99%
“…According to Haile & Kang, incubation time is one of the factors that influences pectinase enzyme production [12]. It is said that a higher pectinolytic index can be used as an indication of higher enzyme activity [18]. However, it requires further quantitative assay to exactly know the enzyme activity of each isolate.…”
Section: Selection Of Pectinolytic Yeastmentioning
confidence: 99%
“…Cellulase may be produced by several microorganisms: actinomycetes, bacteria, and fungi. Each cellulolytic microorganism has a difference in the cellulase activity produced [75] A study by [42] found that Aspergillus niger produced the highest glucose concentration with the highest enzymatic activity (0.13 U/ml), followed by a monoculture of Trichoderma reesei (0.11 U/ml). Besides, [42] reported that Penicillium citrinum and Bacillus subtilis have the activity of 1.72 IU/ml and 2.8 IU/gds, respectively.…”
Section: B Analysis Of Sugar Content 1) Glucose Quantification By Dns...mentioning
confidence: 99%